The Journey towards English Syllabi Unification. : The Case of a Private Colombian University - Villamizar Castrillón, Leidy Johanna; Herreño-Contreras, Yomaira Angélica; Mendieta-Ramírez, Herberth Alfonso (Colombian Applied Linguistics Journal, 2024)
The aim of this paper is to describe the process undertaken by Curriculum Coordinators to design and update English syllabi across all Language Institutes at Universidad Santo Tomás (USTA) in Colombia. It outlines the foundational reasons for updating university syllabi to establish a cohesive set of five English syllabi corresponding to the undergraduate programs’ five English levels at USTA. These programs align with the Learning Assessment System (SEA in Spanish), the University Pedagogical Model, and international standards aimed at fostering communicative and intercultural competences in English as a Foreign Language (EFL). This academic endeavor was grounded in the principles of action research and involved gathering data from institutional documents, as well as surveying the perceptions of directors and curriculum coordinators regarding the English syllabi. The process also incorporated collaborative work as a strategy to consolidate a common framework for English syllabi at USTA. Thus, the design and updating of English syllabi has allowed all the university headquarters and branches to set a common guiding ground for English teaching and learning processes. This initiative has also contributed to the standardization of competences, learning goals, contents, didactic activities, times, outcomes, and assessment for each academic term within the five English levels offered.